BEYOND PILGRIMAGE: Exploring the Dynamic Spirituality of the Hajj for Shaping Social Engagement in Rural Indonesia - Moh Soehadha; Ustadi Hamsah; Khairullah Zikri (State Islamic University North Sumatra, 2026)
This article examines the concept of dynamic spirituality embedded in the hajj by exploring how pilgrimage practices extend beyond individual piety to shape forms of social engagement in rural Muslim communities in Indonesia. Drawing on qualitative fieldwork conducted in Lombok and Madura, this study employs participant observation and in-depth interviews, analyzed through anthropological and phenomenological approaches to the study of religion. The findings demonstrate that the hajj functions not merely as a transcendent act of worship but as a socially embedded ritual that generates communal meanings and relationships. First, the meaning of the hajj shifts from a purely sacred obligation toward a socio-cultural phenomenon that reorganizes social status and moral authority within local communities. Second, the ritual process undergoes festivalization, wherein local cultural expressions reinterpret and publicly celebrate the hajj, reinforcing collective identity. Third, the hajj serves as a form of social adhesive, fostering inter-group solidarity and mediating social relations across kinship, class, and communal boundaries. This study argues that the dynamic spirituality of the hajj reveals its dual role as both a devotional practice and a catalyst for social cohesion, contributing to broader discussions on lived Islam, ritual transformation, and religion’s role in sustaining social integration in contemporary rural societies.